Place attachment to contemporary public-funded mosques in Malaysia - Najafi, Mina (2012)
Place Attachment has been defined as an affirmative expressive bond between people and their surroundings, in terms of psychological well-being. Within the context of religious places, not only spiritual concepts, but also the architectural features of the space could play important roles in forming users’ place attachment. This research investigated Malaysian [mosque] users’ attachment to contemporary public-funded mosques in Malaysia. The study adapted a sequential mixed research methodology for investigating this attachment. In order to develop the research variables of the final survey, 23 people were interviewed within the selected mosques. In order to further formulate the content of the final questionnaire, the systematic field observations and content analysis on the results of the interviews were conducted to identify the architectural characteristics and afforded activities of the selected mosques. A total of 288 respondents participated in the conducted survey. The results revealed that Malaysian users have strong emotional attachment to all studied mosques, due to their significance as religious and cultural places. However, there was no evidence to show that the architectural styles of the selected mosques could significantly affect the users’ Place Attachment. Finally, the results indicated that the respondents were strongly attached to the existing social links to individual experiences, religious status of the places, aesthetical aspects of the architectural elements, spatial order, pleasant surroundings, the supportive facilities and equipment, and upkeep. Employing environmental psychology, this research provided theoretical recommendations to reveal the essential components of the significance of Islamic built environments. These recommendations could become a reference for designers and scholars for leveraging local Islamic identity in the context of Malaysia as a fast growing Islamic country. The reinforced Islamic identity within the public environments can also improve the people’s environmental affections and their contributions toward the society.